(untitled) (Journal of Economic Research & Business Administration, 2016)
This article discusses the functioning of Kazakhstan’s foreign trade and make it the main means of state regulation, also this new management system requires to create a modern customs service and develop traditional customs regulations. The main purpose of these requirements, maintaining targeted fiscal policy, regulation of external trade and the economic security of the Republic in the sphere of the customs authority, to solve the basic problem and to find a more effective option development. Review of the functioning of Kazakhstan’s economy in its first year of existence of the Customs Union shows that, along with the elimination of some trade barriers between joining the customs Union countries, difficulties arose because of the inconsistent tariff policy, the need to prepare new documents, etc. that negatively affects the activity of Kazakhstani companies. To address these constraints requires serious joint work of governmental bodies of all countries-participants of the CU with the obligatory account the views of relevant business communities.